Cerebrospinal fluid-related tissue damage in multiple sclerosis patients with iron rim lesions - Wittayer, Matthias Sebastian; Weber, Claudia Ellen; Kittel, Maximilian; Platten, Michael; Schirmer, Lucas; Tumani, Hayrettin; Gass, Achim; Eisele, Philipp (Multiple sclerosis journal, 2023)
Background: In multiple sclerosis (MS), iron rim lesions (IRLs) are associated with pronounced tissue damage, higher disease severity and have been suggested as an imaging marker of chronic active inflammation behind the blood-brain barrier indicating progression. Furthermore, chronic intrathecal compartmentalized inflammation has been suggested to be a mediator of a cerebrospinal fluid (CSF)-related tissue damage. - Objective: To investigate CSF markers of intrathecal inflammation in patients with at least one IRL compared to patients without IRLs and to investigate tissue damage in lesions and normal-appearing white matter (NAWM) with proximity to CSF spaces. - Methods: A total of 102 patients (51 with at least 1 IRL and 51 age-/sex-matched patients without IRL) scanned with the same 3T magnetic resonance imaging (MRI) and having CSF analysis data were included. - Results: Patients with at least one IRL had higher disability scores, higher lesion volumes, lower brain volumes and a higher intrathecal immunoglobulin G (IgG) synthesis. Apparent diffusion coefficient (ADC) values in IRLs were higher compared to non-IRLs. We observed a negative linear correlation of ADC values in all tissue classes and distance to CSF, which was stronger in patients with high IgG quotients. - Conclusion: IRLs are associated with higher intrathecal IgG synthesis. CSF-mediated intrathecal smouldering inflammation could explain a CSF-related gradient of tissue damage.